Ground state structure of BaZrO3: a comparative first-principles study - Bilic, Ante; Gale, Julian (American Physical Society, 2009)
First-principles calculations, based on density-functional theory, are exploited to investigate the nature of the ground-state structure of barium zirconate. The experimentally observed simple-cubic structure is found to be dynamically unstable against an antiferrodistortive transformation. This instability manifests itself through imaginary frequency modes along the whole R-M edge of the Brillouin zone. The computations predict an orthorhombic crystal structure of the material, only slightly distorted from the cubic lattice, with an eight times larger unit cell and alternate ZrO6 octahedra slightly rotated in opposite directions around the Cartesian axes. The apparent disagreement with some of the previous first-principles results regarding the nature of the ground-state structure is considered in detail. The neglect of the barium 5s2 and 5p6 electrons in the valence configuration of Ba is found to be responsible for the previously reported erroneous results.